2021
DOI: 10.1002/cncr.33627
|View full text |Cite
|
Sign up to set email alerts
|

The intersection of racism, discrimination, bias, and homophobia toward African American sexual minority patients with cancer within the health care system

Abstract: The creation of a racist‐free, prejudice‐free, bias‐free health care system is our individual and collective responsibility. Applying a health equity lens will guide us toward dismantling inequitable treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…One can understand how AI could use features associated with SRR from medical images captured via visible light that incorporate patients' skin tone (eg, melanoma screening). 5,9 This has similarly been observed in color retinal fundus images (RFIs) (Figure 1). 6,7,10 One workaround has been to use preprocessing methods, such as AI-based u-nets, or convolutional neural networks (CNNs) that provide precise segmentation for biomedical images, for automated segmentation of relevant retinal biomarkers, such as the retinal vasculature, hemorrhages, or neovascularization.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…One can understand how AI could use features associated with SRR from medical images captured via visible light that incorporate patients' skin tone (eg, melanoma screening). 5,9 This has similarly been observed in color retinal fundus images (RFIs) (Figure 1). 6,7,10 One workaround has been to use preprocessing methods, such as AI-based u-nets, or convolutional neural networks (CNNs) that provide precise segmentation for biomedical images, for automated segmentation of relevant retinal biomarkers, such as the retinal vasculature, hemorrhages, or neovascularization.…”
supporting
confidence: 68%
“…One can understand how AI could use features associated with SRR from medical images captured via visible light that incorporate patients’ skin tone (eg, melanoma screening) . This has similarly been observed in color retinal fundus images (RFIs) (Figure 1).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Intersectionality and intersectional identities received growing attention during the reviewed publication period. Patients with intersecting identities may face even more complex cancer care challenges than other minority patients and chosen family members [5 ▪▪ ]. For an example, an editorial stated that SGD African Americans face multiple healthcare disparities due to the role racism and discrimination has played over decades in policy making and medical practice [5 ▪▪ ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with intersecting identities may face even more complex cancer care challenges than other minority patients and chosen family members [5 ▪▪ ]. For an example, an editorial stated that SGD African Americans face multiple healthcare disparities due to the role racism and discrimination has played over decades in policy making and medical practice [5 ▪▪ ]. This notion was confirmed in a recent cross-sectional survey which revealed that 29% of Black sexually diverse (SD) women with breast cancer chose to delay care due to barriers such as past negative healthcare encounters, other priorities or struggles relating to scheduling an appointment [6 ▪ ].…”
Section: Resultsmentioning
confidence: 99%